Detection of ROS Generated by UV‐C Irradiation of CdS Quantum Dots and their Effect on Damage to Chromosomal and Plasmid DNA. Issue 4 (21st December 2017) - Blaškovičová, Jana; Sochr, Jozef; Koutsogiannis, Anastasios; Diamantidou, Dimitra; Kopel, Pavel; Adam, Vojtech; Labuda, Ján
Abstract: Different sensitivity of various types of DNA to damage and mutation requires a study of effects of chemical and physical factors on integrity of individual DNA structures. Oxidation stress induced by photoactivated nanoparticles including quantum dots is considered to be the main mechanism of their potential risks. In this work, spectrophotometric indicators of reactive oxygen species (ROS) 4‐chloro‐7‐nitrobenzo‐2‐oxa‐1, 3‐diazole (NBD−Cl) and α‐diphenyl‐β‐picrylhydrazyl (DPPH), electrochemical DNA‐based biosensors with the thiol‐capped CdS quantum dots (CdS QDs) immobilized over the chromosomal (ct DNA) and plasmid (pUC19) DNA biorecognition layers and agarose gel electrophoresis were used (i) to detect ROS generated at the UV‐C irradiation (λ=254 nm) of CdS QDs and (ii) to assess and evaluate their effect towards the chromosomal and plasmid dsDNA structure. Voltammetric and impedimetric measurements revealed a deep degradation of DNA attached to the glassy carbon electrode surface with a stepwise decrease of the portion of survived pUC19 and ct DNA after 60 s to 2400 s irradiation time up to 47 % and to 32 %, resp., comparing to the portion in the absence of CdS QDs reaching 58 % and 40 %, resp. Agarose gel electrophoresis supported the damage to plasmid and chromosomal DNA demonstrating double strand breaks. A decrease in the stability of DNA types towards degradation by ROS in order pUC19>calf thymus>salmon sperm dsDNA has been found. Abstract :